2020
DOI: 10.1101/2020.04.20.050518
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Time-resolved cryoEM using Spotiton

Abstract: 28We present an approach for preparing cryoEM grids to study short-lived molecular states. 29Using piezo electric dispensing, two independent streams of ~50 pL sample drops are 30 deposited within 10 ms of each other onto a nanowire EM grid surface, and the mixing 31 reaction stops when the grid is vitrified in liquid ethane, on the order of ~100 ms later. We 32 demonstrate the utility of this approach for four biological systems where short-lived 33states are of high interest. 34 38 Chen, J. et al. E. coli Tr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…It has the disadvantage of using relatively large volumes for each grid, such as hundreds of nanolitres up to one microlitre, although it may be possible to reduce this volume further. Alternative sample-application methods include the inkjet approach implemented in the Spotiton device (Jain et al, 2012;Dandey et al, 2018) and the microfluidic sprayers used with several time-resolved specimen-preparation devices (Feng et al, 2017;Kaledhonkar et al, 2018;Kontziampasis et al, 2019;Lu et al, 2014;Dandey et al, 2020). Through-grid wicking could also prove useful for preparing optimal ice when applying nanolitre samples to a grid with a microcapillary (Arnold et al, 2016(Arnold et al, , 2017 or from a solid surface (Ravelli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It has the disadvantage of using relatively large volumes for each grid, such as hundreds of nanolitres up to one microlitre, although it may be possible to reduce this volume further. Alternative sample-application methods include the inkjet approach implemented in the Spotiton device (Jain et al, 2012;Dandey et al, 2018) and the microfluidic sprayers used with several time-resolved specimen-preparation devices (Feng et al, 2017;Kaledhonkar et al, 2018;Kontziampasis et al, 2019;Lu et al, 2014;Dandey et al, 2020). Through-grid wicking could also prove useful for preparing optimal ice when applying nanolitre samples to a grid with a microcapillary (Arnold et al, 2016(Arnold et al, , 2017 or from a solid surface (Ravelli et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to trapping transient intermediates, rapid sample preparation has found to have other benefits. By preparing the sample in a few milliseconds, we and others found that the sample did not strongly concentrate at the airwater interfaces (Ma ¨eots et al, 2020;Dandey et al, 2020), although Klebl, Gravett et al (2020) provide conflicting observations. This is a well known effect that can hinder many sample-preparation methods (D'Imprima et al, 2019;Klebl, Gravett et al, 2020;Glaeser, 2018).…”
Section: Topical Reviews 5 Benefits Of Rapid Sample Preparationmentioning
confidence: 85%
“…In this study, we present a major step in the development of time-resolved structural studies, by developing a reliable and robust methodology for the initiation, synchronisation, and freeze-trapping of biochemical reactions onto cryo-EM sample support grids for subsequent analysis. There have been other developments of time-resolved cryo-EM methods 22,23,26,[53][54][55] , including a very recently reported adaptation of existing technology, Spotiton, for time-resolved studies 56 . Some devices already enabled outstanding contributions to resolving unknown biochemistry 26,54,55 , however important steps remain to be improved for the general usability of trEM.…”
Section: Discussionmentioning
confidence: 99%